2018
DOI: 10.1016/j.arth.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Hypesthesia and Kneeling Ability After Total Knee Arthroplasty: A Randomized Controlled Trial Comparing Anterolateral and Anteromedial Skin Incision

Abstract: Compared with anteromedial skin incision, anterolateral skin incision may provide less cutaneous hypesthesia and better kneeling ability after TKA without increasing complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 31 publications
(43 reference statements)
0
24
1
Order By: Relevance
“…53 A randomized controlled trial (RCT) found that patients who received an anterolateral skin incision had a smaller area of cutaneous hypesthesia and better observed kneeling ability compared to patients with an anteromedial skin incision. 54 The findings from these studies indicate that skin incision may have an impact on kneeling ability through numbness. Many studies have compared the clinical outcome of fixed vs mobile-bearing TKR designs; however, few studies have evaluated kneeling ability, and those that have report conflicting results.…”
Section: Aetiologymentioning
confidence: 89%
“…53 A randomized controlled trial (RCT) found that patients who received an anterolateral skin incision had a smaller area of cutaneous hypesthesia and better observed kneeling ability compared to patients with an anteromedial skin incision. 54 The findings from these studies indicate that skin incision may have an impact on kneeling ability through numbness. Many studies have compared the clinical outcome of fixed vs mobile-bearing TKR designs; however, few studies have evaluated kneeling ability, and those that have report conflicting results.…”
Section: Aetiologymentioning
confidence: 89%
“…However, the effects on clinical outcomes are unknown. There have been speculations that lack of sensation around a total knee incision may result in poor patient outcomes, difficulty with day-to-day activities such as kneeling, and overall worse patient satisfaction [11][12][13][14][15]18].…”
Section: Discussionmentioning
confidence: 99%
“…The unknown effects of skin numbness have driven some surgeons to explore alternative approaches and minimally invasive techniques [3,7,15,19]. Tsukada et al [15] demonstrated better kneeling ability and lower occurrence of skin numbness after an anterolateral approach than a traditional midline incision. Although the authors did not report any additional complications during their follow-up, long-term effects of an anterolateral approach are still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No pneumatic tourniquet was used during the study period. An anterolateral incision was used in all surgeries [14]. A subvastus approach without patellar eversion was used except in patients with valgus knee alignment, for whom a lateral approach was used.…”
Section: Methodsmentioning
confidence: 99%